Analisis Polimorfisme Gen dan Aplikasinya Dalam Klinik - Corry N. Mahama; Dwi A. Suryandari (Jurnal Biologi Papua, 2023)
Gene polymorphism refers to a variation in DNA sequence that occurs in a population with a frequency of 1% or higher. Polymorphism may be a variation in single nucleotide (SNP) or a variation in some repetitive DNA sequences (length polymorphism). Several methods can be used to analyze polymorphism, included Polymerase Chain Reaction (PCR), DNA sequencing from the conventional method to more sophisticated method such as Next Generation Sequencing (NGS), fluorescence in situ hybridization, comparative genomic hybridization, and DNA microarrays. Recently, more studies have been carried out to find the relationship between polymorphism and disease severity or prognosis, response to various drugs, susceptibility to environtmental factors such as toxins, susceptibility to infections and cancers.Key words: DNA; gene polymorphism; PCR; clinic.